Concert Hall Sound Clarity: A Comparison of Auditory Judgments and Objective Measures - MIŚKIEWICZ, Andrzej; ROGALA, Tomira; ROŚCISZEWSKA, Teresa; RUDZKI, Tomasz; FIDECKI, Tadeusz (Archives of Acoustics, 2012)
The purpose of the study was to compare auditory judgments of sound clarity of music examplesrecorded in a concert hall with predictions of clarity made from the impulse response signal recordedin the same hall. Auditory judgments were made with the use of two methods: by rating sound clarityon a numerical scale with two endpoints, and by absolute magnitude estimation. Results obtained byboth methods were then compared against the values of clarity indices, C80 and C50, determined fromthe impulse response of the concert hall, measured in places in which the microphone was located duringrecording of music examples. Results show that auditory judgments of sound clarity and predictions madefrom the C80 index yield a similar rank order of data, but the relation between the C80 scale and perceivedsound clarity is nonlinear. The data also show that the values of C80 and C50 indices are in very closeagreement.